Initiating a Meaningful Assessment of Early Childhood Development during the Covid-19 Pandemic - Luluk Rochanah (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2021)
Assessment of early childhood development during the COVID-19 pandemic really needs to be done in order to monitor the process and progress of children's learning optimally and continuously through a systematic, periodic and continuous process to collect data, conduct analysis, document and make decisions and make reports on developments. child. This study uses a qualitative approach based on a phenomenological perspective, with interview, observation, and documentation techniques. This study aims to determine the growth and development of Religious and Moral Values, Physical Motor, Cognitive, Language, Social Emotional and Art, obtain initial information related to obstacles or disorders in child growth and development, how to stimulate services with children's developmental needs, provide appropriate support appropriate for children, how to stimulate services with children's development needs, provide appropriate support to children from parents when learning from home.